Burnout in Software Projects: An Analysis of Stack Exchange Discussions - Paula, Antônio Carlos M. de; Muakad, Carlos Frederico J.; Freire, Sávio; Spínola, Rodrigo; Mendonça, Manoel (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2024: Anais do XXIII Simpósio Brasileiro de Qualidade de Software, 2024)
Context. Burnout is a psychological issue defined by emotional exhaustion, depersonalization, and reduced personal fulfillment in the workplace. It has emerged as a significant concern in the IT sector, emphasizing the need for more research on effective ways to manage burnout. Aims. To investigate, from the point of view of software practitioners, the symptoms, causes, and effects of burnout in the IT industry. Method. We collected and analyzed 54 discussions from two Stack Exchange communities. Results. We identified that software practitioners have discussed different types of burnout, such as ‘frenetic’ (high dedication or active coping style), ‘underchallenged’ (moderate dedication), and ‘worn out’ (low dedication or passive coping style). Tiredness, lack of motivation, and stress are the main symptoms of burnout, while work overload, dissatisfaction, and short deadlines are the primary causes. The effects of burnout mainly impacts the productivity and quality of software projects. Better task management and physical or mental relaxing activities are the ways to resolve burn out cases. Conclusion. We organize the body of knowledge about burnout into a conceptual diagram, supporting software professionals in defining strategies to prevent and mitigate burnout in their projects.